Role of Teachers in Supply Chain Education in Indonesia - Obsatar Sinaga; Heri Heryono; Neneng Susanti; Noor H. Jabarullah (International Journal of Supply Chain Management, 2019)
Creating student’s interest in supply chain learning is most crucial and significant to achieve better outcomes. It is challenging for the teachers to develop student’s interest in learning. Teachers have been developing and establishing new techniques to stimulate students interest. Therefore, in this direction, the main purpose of this study is to ensure the student’s interest in supply chain education with the help of teacher’s willingness and ability. Furthermore, the moderating role of fun learning by the teacher for enhancing the student’s interest has also been discussed. Besides this was a cross sectional study. Sample size of this study was 300 students of schools. 5-point Likert scale was used to collect the response. Smart PLS software was used to analyze the data. Findings of this study were that teacher’s willingness and ability created interest with the help of fun learning which increases supply chain performance (SCP). Further, it’s also been concluded that fun learning put a strong effect in enhancing student’s creativity and SCP.